Urgensi Teori Hierarki Kebutuhan Maslow dalam Meminimalisir Prokrastinasi Akademik Di Kalangan Mahasiswa - Muhibbin, Muhibbin; Marfuatun, Marfuatun (Universitas Hamzanwadi, 2020)
This paper aims to examine Abraham Maslow's hierarchical theory of needs and academic procrastination behavior, how to implement the hierarchy of needs theory as a solution to overcome academic procrastination behavior among students. the implications of Maslow's hierarchy of needs theory in the learning process. This research is a type of library research, (Reseaceh library). Data collection techniques used by researchers to collect data using documentation methods and one data source, namely secondary data sources. For data analysis using content analysis techniques (content analysis). The results of the research are: the hierarchy of needs theory is a theory of multilevel needs while academic procrastination is the lack of fulfillment of student responsibilities related to timely in the educational process. The implementation of the hierarchy of needs theory as a solution to overcome academic procrastination behavior among students so that physiological needs, security, feelings of love, respect and self-actualization of students can be fulfilled by fulfilling these five needs, student academic procrastination behavior can be overcome and the implications can stimulate students to take new opportunities. to improve themselves and, as a result, to improve their current achievements. It can also have a positive impact on them towards a better direction, for growth and provide benefits for themselves in the future.